2011
DOI: 10.1002/hbm.21066
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐patterns of language network reorganization in pediatric localization related epilepsy: A multisite study

Abstract: To study the neural networks reorganization in pediatric epilepsy, a consortium of imaging centers was established to collect functional imaging data. Common paradigms and similar acquisition parameters were used. We studied 122 children (64 control and 58 LRE patients) across five sites using EPI BOLD fMRI and an auditory description decision task. After normalization to the MNI atlas, activation maps generated by FSL were separated into three sub-groups using a distance method in the principal component anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 65 publications
1
68
0
Order By: Relevance
“…With the exponential increase in the number of connectivity studies in patients with epilepsy, different changes in the topology of the FCN constructed using different network measurements were reported, however few studies [23,58] examine the changes in FCN's of pediatric populations. The other important reason to focus on this population was the finding in [12] which supports that regular treatment of epilepsy may or may not treat childhood epilepsy.…”
Section: Introductionmentioning
confidence: 98%
“…With the exponential increase in the number of connectivity studies in patients with epilepsy, different changes in the topology of the FCN constructed using different network measurements were reported, however few studies [23,58] examine the changes in FCN's of pediatric populations. The other important reason to focus on this population was the finding in [12] which supports that regular treatment of epilepsy may or may not treat childhood epilepsy.…”
Section: Introductionmentioning
confidence: 98%
“…The MRI data were acquired as control data for the Multi-Site Pediatric Network for fMRI Mapping in Childhood Epilepsy consortium (You et al, 2011). Both sites used the same model of scanner (Siemens 3 T Trio) and identical imaging parameters, and a study utilizing the same datasets demonstrated minimal data differences across sites and scanners (You et al, 2011). Standard Wechsler Abbreviated Scale of Intelligence (WASI) tests were scheduled, but not enforced (to facilitate participant recruitment), for all subjects in order to collect the IQ scores.…”
Section: Participants and Acquisition Parametersmentioning
confidence: 99%
“…Many researchers have tried to investigate the reproducibility and reliability of the acquired networks through different imaging protocols [139,149,150] , different imaging sites [151,152] , and different parameters for constructing networks [19,153] . However, this is still an open question for the Brainnetome era [12] .…”
Section: Future Directions Of Dmri For Brainnetomementioning
confidence: 99%